THE PARTY AFFILIATION OF THE EUROPEAN PARLIAMENT: THE FUTURE OF THE EUROPEAN UNION - Вархов, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The present article deals with the peculiarities conduct of elections to the European Parliament in 2014. The paper investigates the chief factors that have influenced the election results and motived citizens of the European Union member states to vote for some political force. The data were analyzed the influence of the party groups’ activity on the internal and foreign policy of the EU.